KONTRIBUSI RETRIBUSI TERMINAL AWEH TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN LEBAK - Pindonta Nalsal; Nurhaini Nurhaini; Elma Octarisa (Universitas La Tansa Mashiro, 2017)
This study describes the Lebak District Transportation Department every day always carry out levies retribution of the terminal on public transportation, it's just that the activity in income to the original income of the region lacks a big influence, this is based on several factors such as frequent menghamabat levy collection activities and the number of unsuccessful elements that are less responsible for the implementation of these charges, so the target. The purpose of this researcher is (1) To mengetathui Terminal Retribution Contribution to the district service lebak to know the income of the Region (PAD), Lebak District (3) To Know how much Influence The Contribution of Terminal of Aweh On Local Own Revenue (PAD) of Lebak Regency.